Implementasi Program Mandiri Belajar dalam Kurikulum Merdeka Pada PAI dan Budi Pekeri di SMP Queen Al Falah Ploso Kediri - Achmad Safichrudin (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
Along with the changing times that are increasingly advanced, the Ministry of Education, Culture and Research recently launched a new curriculum, namely the Independent Curriculum so that every school is required to be able to follow this curriculum change. Queen Al Falah Junior High School is one of the schools that implements this curriculum, of course it will greatly affect the programs in this junior high school. One of them is the learning method. The objectives of this study are; first, to explain the implementation of the independent learning program in the independent curriculum in Islamic Religious Education and Ethics at Queen Al Falah Ploso Junior High School, second, to explain the implications of the implementation of the independent learning program in the independent curriculum in Islamic Religious Education and Ethics at Queen Al Falah Ploso Junior High School. The approach in this research is descriptive qualitative which is carried out with three data collection techniques, namely; observation, interviews and documentation. The analysis technique in this research is by using qualitative data analysis which consists of: 1) data reduction; 2) data presentation; and 3) conclusion, where the process takes place circularly during the research. The results of this study are; first, the procedure for continuing to implement K13 then what is done to implement the independent learning program in the independent curriculum in PAI and Budi Pekerti Education is 3, namely implementing P5 even though it is not perfect, holding independent curriculum workshops and specifically PAI and Budi Pekerti Teachers learn through PMM (Platfrom Merdeka Mengajar). The method used to implement the independent learning program at Queen Al Falah Junior High School in PAI and Budi Pekerti is the differential method. The second result is the implications arising from the implementation of the independent learning program, namely 1) Increase student success. 2) Appreciate individual differences, 3) Improve Connection with Lesson Content, 4) Improve Social Skills. As for PAI and Budi Pekerti Teachers, they are more creative and innovative in delivering material.